High-Gain Modified Antipodal Vivaldi Antenna for Ultra-Wideband Applications - S.A., Adamu; T., Masri; Wan Azlan, Wan Zainal Abidin; Kismet, Hong Ping; S. A., Babale (Universiti Teknikal Malaysia Melaka, 2018)
In this paper, the design of a high gain modified antipodal Vivaldi antenna (HG-MAVA) for ultra-wideband applications is presented. The proposed antenna designed on a low-cost FR4 substrate with a thickness of 1.6mm was realized by incorporating a combination of exponential slot edge corrugation on the radiating flare and a high permittivity dielectric director in the flare aperture of a conventional antipodal Vivaldi antenna (CAVA). Compared to the CAVA, the proposed antenna extends the lower end frequency limit of the CAVA to 2.15 GHz. Improvement in realized gain is also achieved throughout the 2.15 GHz to more than 11 GHz operating frequency band of the proposed antenna with the highest improvement of 1.61 dBi at 7 GHz. The surface current distribution and the radiation pattern of the proposed antenna were studied to further characterize the performance of the antenna.